Advances and controversies in frontotemporal dementia: diagnosis, biomarkers, and therapeutic considerations. Issue 3 (March 2022) - Boeve, Bradley F; Boxer, Adam L; Kumfor, Fiona; Pijnenburg, Yolande; Rohrer, Jonathan D
Summary: Frontotemporal dementia comprises a group of clinical syndromes that are characterised by progressive changes in behaviour, executive function, or language. The term frontotemporal lobar degeneration encompasses the neurodegenerative diseases that give rise to these clinical syndromes and involve proteinopathies associated with frontotemporal network dysfunction. Improvements in clinical, genetic, and molecular characterisation have provided new insights into frontotemporal dementia and frontotemporal lobar degeneration, with a much broader range of signs and symptoms at presentation than has been previously considered. Accurate and early diagnosis of frontotemporal dementia is now a possibility due to development of neuropsychological measures with a special focus on social cognition. Advances in plasma and CSF biomarkers, and innovations in structural and functional imaging, will prove useful for future clinical trials in people with frontotemporal dementia.